Semiotics of Music by the Band Pyong-Pyong as a Tool for Social Criticism: an Analysis of the Symbolism in the Lyrics of the Album "Pigza" - Pradipta, Nareswara Bima; Jazuli, Muhammad; Sinaga, Syahrul Syah (Journal La Sociale, 2023)
Music serves not only as an artistic expression but also as a medium to convey important social and political messages. For example, the punk band Pyong-Pyong from Semarang City uses music to critique social conditions. Over the span of two decades, the band has undergone transformations in its members and musical style, with their latest album, "Pigza," showcasing their evolution in the music industry. This research analyzes the symbolism in the lyrics of the songs from "Pigza" used for social critique. Using a qualitative approach and Roland Barthes' semiotic analysis method, this study explores the symbolism in the lyrics of "Pigza" songs. Findings indicate that four songs in the album — "Jika," "Mereka," "Kurang Piknik," and “Kita Ingin Damai” — articulate deep messages about social conditions and individual experiences in modern society.